INNOVATION OF PEEL-OFF FACE MASKS MADE WITH SPIRULINA (Arthospira platensis) TOWARDS A CREATIVE ECONOMY - Alia, Rahmah; Jumrodah, Jumrodah; Swestyani, Sondra (Universitas Medan Area, 2025)
Facial skin care, especially facial masks, has become part of the modern lifestyle, as the younger generation becomes increasingly aware of the importance of a healthy appearance. One natural ingredient that is widely used in skin care products is Spirulina platensis, a microalgae that is rich in nutrients and has various benefits, such as antioxidant, anti-inflammatory and antibacterial. This research aims to develop a peel off facial mask made from Spirulina platensis which is equipped with essential oil to improve the quality of skin care which is a major contribution to the development of natural cosmetics so that it can become an attractive alternative in the cosmetics industry. The method used in this research is an experimental method with five mask treatments. The results of the ANOVA test showed that there were significant differences in the aroma, color and consistency of the mask. Masks with Vanilla essential oil (F3) are preferred because of their more pleasant aroma, while masks with Sakura essential oil (F4) have the most preferred color. This research shows the potential of Spirulina platensis as an active ingredient in peel-off masks, which can be an attractive alternative in the cosmetics industry, as well as supporting a creative economy based on natural ingredients.